PENINGKATAN KOMPETENSI PROFESIONAL GURU DALAM MENYUSUN LAPORAN PENELITIAN TINDAKAN KELAS MELALUI MODEL PEMBINAAN CLCK (CONTOH, LATIHAN, CONTROL, KERJA MANDIRI) BERBASIS MENTORING DI SDN 22 SUNGAI LIMAU - Gusniati Gusniati (JURNAL MANAJEMEN PENDIDIKAN, 2017)
ABSTRACTThis study aims to describe and obtain information about the improvement of professional competence of teachers in preparing classroom action research reports through CLCK development model (Example, Exercise, Control, Self Employment) based mentoring at SDN 22 Sungai Limau. This research is a school action research with research procedure including planning, action, obeservasi and reflection. This study consists of two cycles with four meetings. The subjects were 7 teachers of SDN 22 Sungai Limau. The data were collected using obeservation sheets. Data were analyzed using percentages. The results showed that mentoring model based on CLCK could improve teachers' ability in preparing classroom action research reports at SDN 22 Sungai Limau. Analysis on the quality of PTK reports made by teachers shows that the professional competence of teachers in preparing classroom action research reports increases from cycle I to cycle II. Teacher professional competence in preparing class action research report on cycle I is 78,14 (enough) increase to 85,42 (good) in cycle II with increase of equal to 7.00 points.Keywords: Professional Teacher Competency, PTK Report, CLCK mentoring based mentoring model